Insights into the roles of intergranular carbides in the initiation of intergranular stress corrosion cracking of alloy 690 in simulated PWR primary water. (March 2022) - Kuang, Wenjun; Feng, Xingyu; Yue, Han; Was, Gary S.; Hao, Xianchao
Abstract: The effect of intergranular carbides on the stress corrosion crack (SCC) initiation of alloy 690 in high-temperature hydrogenated water was systematically studied. Irrespective of the aging temperature, the resistance to SCC initiation continuously increases with increasing carbide coverage. The understanding of carbide effects was further advanced. Mechanically, the carbide mitigates the breach of surface oxide film over the grain boundary by suppressing the local apparent plastic strain. The carbide also greatly diminishes grain boundary migration by retarding the diffusion of Cr. More importantly, it decomposes when exposed to the environment and serves as Cr source for forming protective oxide film. Graphical Abstract: ga1 Highlights: The resistance to PWSCC initiation of Alloy 690 is increasingly enhanced by carbide. Carbides suppress the plastic strain and preserve oxide film near the grain boundary. Carbides greatly diminish grain boundary migration by retarding the diffusion of Cr. Carbides decompose when exposed to the environment and provide Cr for oxidation.